Analisa Faktor-Faktor Yang Mendorong Penggunaan Sistem Informasi Kepegawaian (SIPEG) : Studi Kasus Politeknik Negeri Padang - Ade Irma Suryani; Achmad Nizar Hidayanto (Jurnal Ilmiah Poli Rekayasa, 2015)
Padang State Polytechnic is one of the best vocational Polytechnic in Sumatera. As the best college, Padang State Polytechnic has implemented several information systems; such as the Information System in the Human Resource Civil Service Department. However, the system still was not optimally utilized within the institution as a tool to support data processing and strategic tool to gain strategic advantages and to support the growth of the organization to a better level. This research was conducted to analyze the factors that encourage the usage of information system in the Human Resource Civil Service Department in PNP. In order to collect data survey, author has sent questionnaires to all faculties including lecturers and administration staffs in Padang State Polytechnic as user of Information System in the Human Resource Civil Service Department. Among 160 questionnaires that were distributed, only 121 questionnaires were returned. Furthermore, the questionnaires were proceeded with the Structural Equation Modeling (SEM) method by using Amos Software v.21. In conclusion, the factors that encourage the usage of Information System in the Human Resource Civil Service Department in PNP are Information Quality, Service Quality and System Quality.